PENYELESAIAN SENGKETA PERKAWINAN TERHADAP HARTA BERSAMA TERKAIT ISTERI NUSYUZ (DURHAKA) DAN AKIBAT HUKUMNYA DI INDONESIA - Razak, Syahrial (Departemen Hukum Perdata, 2018)
The divorce rate in Indonesia is quite high according to the data presented by Religious Jurisdiction Chamber (Badilag) of Indonesian Supreme Court in 2015 there are 96,678 cases of talak petition and 249,578 cases of divorce lawsuit. This article will elaborate the legal consequences of talak petition based on the reasons that the respondent (wife) has committed seditious (nusyuz) against claimant (husband), moreover this article will also reveal empirically the motivation of the wife committed seditious. In most cases, the wife may commit seditious triggered by violent act committed by her husband or marry another woman secretly. When trying such cases, the court must adjudicate carefully and thoroughly the reasons of request for talak which contended by the husband and its background. The careful and thorough trial on the evidences presented by the parties may lead to judgment which just and fair as the settlement of the dispute in divorce cases and distribution of matrimony properties.